Digital Visibility of Tourist Destinations in Sabang: A Composite Index Analysis Using Online Platform Indicators - Nabilah Nabilah; Fachrurrazi Fachrurrazi; Nurhafikin Nurhafikin (Eastasouth Institute, 2026)
The rapid expansion of digital platforms has transformed how tourists search for information, evaluate destinations, and make travel decisions. Consequently, digital visibility has become an increasingly important component of destination competitiveness. However, empirical assessments of the digital visibility of local tourist destinations using cross platform indicators remain limited, particularly in emerging tourism areas such as Sabang, Indonesia. This study assessed the digital visibility of 15 tourist destinations in Sabang using a quantitative descriptive approach. Data were manually collected in May 2026 from Google Maps, TripAdvisor, Instagram, and official websites or dedicated tourism information pages. A composite Digital Tourism Visibility Index (DTVI) was constructed using eight indicators: Google ratings, Google review counts, presence on TripAdvisor, TripAdvisor ratings, TripAdvisor review counts, presence on Instagram, website availability, and the completeness of destination-related digital information. The findings reveal considerable variation in digital visibility across the destinations examined. Iboih Beach recorded the highest DTVI score, followed by the Zero Kilometer Monument and Rubiah Island, whereas several other destinations exhibited relatively limited online representation. These disparities were associated with differences in review volume, cross-platform presence, and the availability and completeness of digital information. This study contributes to digital tourism analytics by developing a practical cross-platform framework for assessing destination level digital visibility. The findings also provide an initial diagnostic basis for destination managers and local governments to formulate more targeted digital promotion and destination management strategies.